Genomic features and evolution of the conditionally dispensable chromosome in the tangerine pathotype of Alternaria alternata. (11th July 2019) - Wang, Mingshuang; Fu, Huilan; Shen, Xing‐Xing; Ruan, Ruoxin; Rokas, Antonis; Li, Hongye
Summary: The tangerine pathotype of the ascomycete fungus Alternaria alternata is the causal agent of citrus brown spot, which can result in significant losses of both yield and marketability for tangerines worldwide. A conditionally dispensable chromosome (CDC), which harbours the host‐selective ACT toxin gene cluster, is required for tangerine pathogenicity of A. alternata . To understand the genetic makeup and evolution of the tangerine pathotype CDC, we isolated and sequenced the CDCs of the A. alternata Z7 strain and analysed the function and evolution of their genes. The A. alternata Z7 strain has two CDCs ( 1.1 and 0.8 Mb, respectively), and the longer Z7 CDC contains all but one contig of the shorter one. Z7 CDCs contain 254 predicted protein‐coding genes, which are enriched in functional categories associated with 'metabolic process' (55 genes, P = 0.037). Relatively few of the CDC genes can be classified as carbohydrate‐active enzymes (CAZymes) (4) and transporters (19) and none as kinases. Evolutionary analysis of the 254 CDC proteins showed that their evolutionary conservation tends to be restricted within the genus Alternaria and that the CDC genes evolve faster than genes in the essential chromosomes, likely due to fewer selective constraints. Interestingly, phylogenetic analysis suggested that four of the 25 genes responsible for the ACT toxin production were likely transferred from Colletotrichum (Sordariomycetes). Functional experiments showed that two of them are essential for the virulence of the tangerine pathotype of A. alternata . These results provide new insights into the function and evolution of CDC genes in Alternaria .